Development of Monoclonal Antibodies Targeting Canine PD-L1 and PD-1 and Their Clinical Relevance in Canine Apocrine Gland Anal Sac Adenocarcinoma - Minoli, Lucia; Licenziato, Luca; Kocikowski, Mikolaj; Cino, Marzia; Dziubek, Katarzyna; Iussich, Selina; Fanelli, Antonella; Morello, Emanuela; Martano, Marina; Hupp, Ted; Vojtesek, Borek; Parys, Maciej; et al. (Cancers, 2022)
Canine apocrine gland anal sac adenocarcinoma (AGASACA) is an aggressive canine tumor originating from the anal sac glands. Surgical resection, with or without adjuvant chemotherapy, represents the standard of care for this tumor, but the outcome is generally poor, particularly for tumors diagnosed at an advanced stage. For this reason, novel treatment options are warranted, and a few recent reports have suggested the activation of the immune checkpoint axis in canine AGASACA. In our study, we developed canine-specific monoclonal antibodies targeting PD-1 and PD-L1. A total of 41 AGASACAs with complete clinical and follow-up information were then analyzed by immunohistochemistry for the expression of the two checkpoint molecules (PD-L1 and PD-1) and the presence of tumor-infiltrating lymphocytes (CD3 and CD20), which were evaluated within the tumor bulk (intratumor) and in the surrounding stroma (peritumor). Seventeen AGASACAs (42%) expressed PD-L1 in a range between 5% and 95%. The intratumor lymphocytes were predominantly CD3+ T-cells and were positively correlated with the number of PD-1+ intratumor lymphocytes (ρ = 0.36; p = 0.02). The peritumor lymphocytes were a mixture of CD3+ and CD20+ cells with variable PD-1 expression (range 0-50%). PD-L1 expression negatively affected survival only in the subgroup of dogs treated with surgery alone (n = 14; 576 vs. 235 days). The presence of a heterogeneous lymphocytic infiltrate and the expression of PD-1 and PD-L1 molecules support the relevance of the immune microenvironment in canine AGASACAs and the potential value of immune checkpoints as promising therapeutic targets.
Keywords: PD-L1; tumor-infiltrating lymphocytes; immunohistochemistry; apocrine gland anal sac adenocarcinoma; dog; PD-1